2011
DOI: 10.1097/sap.0b013e31822484ae
|View full text |Cite
|
Sign up to set email alerts
|

The Course and Variation of the Facial Artery and Vein

Abstract: The main arterial supply of the facial skin envelope is the facial artery which serves as the main pedicle for a number of facial flaps, including a facial transplant graft. This study explored the course of the facial artery and vein, branching patterns, terminations, and anomalous variants. Cadaveric dissections of 201 facial arteries and 198 facial veins were performed. All branches originated from a single facial arterial trunk in 86% of specimens and branching patterns were symmetrical in 53%. The facial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 15 publications
3
69
1
2
Order By: Relevance
“…The facial vein then descends down towards the angle of the jaw where it joins with the anterior branch of the retromandibular vein [9]. In the cadaveric series by Lohn et al [5] the facial vein was absent in only 1% of cases, had a predictable course and was shown to be, on average, 0.7 cm more posterior from the gnathion than the facial artery. The proximity of the two vessels supports their use as first choice recipient artery and vein in cases of free tissue transfer for facial reanimation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The facial vein then descends down towards the angle of the jaw where it joins with the anterior branch of the retromandibular vein [9]. In the cadaveric series by Lohn et al [5] the facial vein was absent in only 1% of cases, had a predictable course and was shown to be, on average, 0.7 cm more posterior from the gnathion than the facial artery. The proximity of the two vessels supports their use as first choice recipient artery and vein in cases of free tissue transfer for facial reanimation.…”
Section: Discussionmentioning
confidence: 99%
“…Standard intraoperative procedure would involve an extended parotidectomy incision on the paralysed side of the face, elevation of the skin flap and exploration for the facial vessels. Exploration would start at the point where they cross the mandible just anterior to the masseter muscle given their consistent position at this point along their course [5]. In cases when a suitable facial artery and/or vein were not identified after detailed exploration, attempts would be made to identify alternative recipient vessels (Figs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2004, Renshaw et al 2 found one case of facial vein draining into the temporal vein in a color Doppler ultrasound study conducted in 100 patients, with a frequency of 1%. More recently, Lohn et al 3 found during anatomical dissections the variation in 2 cases, with a frequency of 2%. Among the 4 previously published cases, 2 cases presented the variation on the right side of the face and 2 cases were not documented, so that no conclusion can be drawn about any predominance of one side over the other.…”
Section: Sirmentioning
confidence: 96%
“…The predominant distribution of the facial artery in the facial region is commonly seen but cannot be predicted. Therefore, it is mandatory to carefully perform a vascular work-up prior to the facial transplantation and unipedicled flap procedure [19]. For the facial transplantation procedure, three-dimensional virtual models of the face are generated on de-identified CT angiography.…”
Section: Surgery Planmentioning
confidence: 99%